Derivational Affix in the Movie "The Gentlemen" by Guy Ritchie: Morphology Study - Restu Wibisana; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to analyze derivational affix in the movie The Gentlemen. The purposes of this research are to find out the types and forms of derivational affix in The Gentlemen movie. The study of derivational affix was interesting to analyze because it affects on the formation of words from simple to complicated. This research used the descriptive qualitative method. In analyzing the data, researcher used the theories about morphology from Haspelmath and Sims (2010), and Lieber (2009). The researcher also used the theories about affixation from Procter (1980). The results of the analysis show there are 133 data types of derivational affix found in The Gentlemen movie consisting: 107 suffixes and 26 prefixes. The dominant of derivational affix in the Gentlemen movie is derivational suffix with the total percentage 78% and then derivational prefixes with the total percentage 22%. Moreover, there are four forms the most derivational affix used in The Gentlemen movie, they are 59 Noun form (44%) then 46 Adjective form (35%), 17 Verb form (13%) and 11 Adverb form (8%).